Algunas características anatómicas y acústicas de tres especies de angiospermas de Huayacocotla, Ver. - Quintanar Isaías, Alejandra; de Icaza Herrera, Miguel; Rivera Nava, Laura; de la Paz Pérez Olvera, Carmen (Instituto de Ecología, A.C., 2016)
Some anatomical features of wood, like vessels, fibres and ray dimensions, were studied. Also axial and tangential sound velocity and Young's moduli, axial, radial and tangential were obtanied of three hardwood species from Huayacocotla, Ver. The results show that pore number, fibre cell wall thickness influence directly the axial sound velocity. Rays are structures which are partly responsible for high values of radial velocity and low values of tangential velocity. It is recommended that Prunus brachybotrya and Cleyera sp are used to substitute Acer species employed in box violin construction.